DETERMINAN KESUKSESAN SISTEM INFORMASI DI RSUD Dr. MOEWARDI - Ermiati .; Didik Setyawan; Waluyo Budi Atmoko; Sugiyarmasto . (Jurnal Bisnis dan Kewirausahaan, 2020)
The study of success information system organized is still a study important in researchs systems information. It is caused by existence of the diversity of the results of research on the success of the the information system in organizations on various research an object that impact on variable user and the weapons of the analysis that adapted to the purposes of research (Delone & Mclean, 2003; Wu & Wang, 2006; Holsapple & Le-post, 2006). The purpose of this research is to test antaseden in the form of satisfaction in building intention use the information at RSUD Dr .Moewardi Surakarta. Research sample areas are employees at RSUD Dr .Moewardi as many as 200 respondents. Sampling technique use two stage clusters random sampling, a measuring instrument use testing spss and the testing of hypotheses use SEM (Structural Equation Modelling) with software AMOS. Based on the results of the analysis showed that all hypothesis supported that is significant the connection between satisfaction with the intention to continue, a significant relation between quality information with satisfaction user, a significant relation between quality the system with satisfaction users, and a significant relation exists between the quality of services with satisfaction users information system